Peran Pentingnya Pengetahuan Tentang Kontrak Kerja Dan Pembentukan Karakter Bagi Siswa Sekolah Menengah Kejuruan (SMK) Dalam Memasuki Dunia Kerja - Dwi Atmoko; Noviriska Noviriska; Sugeng Sugeng; Jantarda Mauli Hutagalung; Otih Handayani; Esther Masri; Adhalia Septia Saputri; Ardhana Ulfa Azis; Septina Rahmi Kinasih (Prodi PGSD Unsultra, 2026)
Vocational High School (SMK) education plays a crucial role in preparing students to enter the workforce. However, despite the provision of technical education and vocational skills, the primary challenge faced by SMK graduates is their readiness to face the demands of the workforce, particularly regarding character and soft skills. Today's workforce prioritizes not only technical skills but also interpersonal skills, discipline, and a strong work ethic. Therefore, character development for SMK students is crucial to increasing competitiveness in the job market. Character education is a crucial aspect of education. A mature SMK student's character can be invaluable capital for entering the workforce. However, this character-building process does not occur solely in the classroom; it requires a holistic approach integrated with various activities and experiences outside the formal curriculum. Therefore, character development needs to be strengthened through more practical and applicable educational programs that can help students understand the importance of values such as responsibility, hard work, and a positive attitude at work. In fact, employment agreements can be made not only in writing but also verbally. However, for fixed-term employment, the agreement must be made in writing to prevent negative consequences at the end of the employment agreement, such as workers demanding reemployment even though the employment agreement has expired, thereby harming the employer. For indefinite-term employment agreements, the employment agreement can also be made verbally, which applies to permanent workers.